PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI - Widaryati, Hany Septiana (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2015)
This research aims to find out: 1) whether there is influence of the leadership toward the employees job satisfaction in the Department of Education Youth and Sports Surakarta; 2) whether there is influence of the working environment toward the employees job satisfaction in the Department of Education Youth and Sports Surakarta; 3) the influences of the leadership and working environment toward the employees job satisfaction in the Department of Education Youth and Sports Surakarta.This research is designed as quantitative research with descriptive method. The population of this research is the whole employees, 80 people, of the Department of Education Youth and Sports Surakarta. The sample taken was 60% of the entire population or 50 employees. The sampling technique used is proportional random sampling while the data collection method applied is questionnaire. The data analysis technique in this research is statistic test using correlation and multiple regression analysis. Based on the data analysis, it can be concluded that: 1) there is significant influence of the leadership toward the employees job satisfaction in the Department of Education Youth and Sports Surakarta; 2) there is significant influence of the working environment toward the employees job satisfaction in the Department of Education Youth and Sports Surakarta; 3) there is significant influence of the leadership and the working environment simultaneously toward the employees job satisfaction in the Department of Education Youth and Sports Surakarta.Keywords: leadership, working environment, job satisfaction